Videofluoroscopia da deglutição : características da deglutição em adultos e idosos - Ferreira, Lígia Brum Motta (2013)
Introduction: The videofluoroscopic swallowing exam (VFSE) allows for the evaluation of the swallowing process, and it is an important method to characterize and compare the different phases of swallowing, to classify the degree of dysphagia, and to identify laryngotracheal penetration/aspiration in adults and in the elderly. Objective: To compare the swallowing characteristics in young and elderly adults who underwent VFSE in two hospitals in southern Brazil. Methods: Retrospective study of individuals aged ≥ 18 years who underwent VFSE in two hospitals in southern Brazil, between May 2010 and May 2012. The evaluation comprised the analysis of the modified protocol (Furkim (1999) and the intake of three food consistencies, liquid, paste-like (nectar) and solid (pudding) contrasted with barium sulfate, according to the National Dysphagia Diet guidelines. Data were analyzed through Pearson s chi-square test, and in case of statistical significance, the test of adjusted residuals was used. Significance was established at p≤0.05. The study was approved by the CEP-PUCRS under number 260.501. Results: We evaluated 553 individuals, from 18 to 98 years, 358 (64,7%) elderly, 51,7% adults, and 64,6% adults who had no pre-established etiologic diagnosis for dysphagia. The elderly with or without etiologic diagnosis for dysphagia presented more involvement in the oral, pharyngeal, and esophageal phases of swallowing when compared to adults from both groups. Regarding the scale of dysphagia severity and the age range of the undiagnosed group, 21,1% of adults presented a higher proportion of normality compared to the elderly (7,9%). When the scale of dysphagia was categorized into four groups (esophageal, normal, within functional limits/ mild dysphagia, and moderate/intense dysphagia), the following facts were observed: a significant association between the dysphagia severity scale and the age range (p=0.001) for the group of individuals without etiologic diagnosis for dysphagia, a higher proportion of normality in adults when compared to the elderly (38-30.2% vs. 22-12.0%), and a higher proportion of individuals classified as within functional limits and mild dysphagia in the elderly when compared to the adults (117-63,6% vs. 56-44,4%). Conclusion: The elderly presented more changes in the characteristics and efficiency of swallowing in the three phases of swallowing and higher levels of dysphagia when compared to adults. In individuals without pre-established diagnosis for dysphagia, the elderly also presented more changes in the characteristics of swallowing, higher levels of dysphagia, and presence of penetration and laryngotracheal aspiration.